Unusual Predation Attempts of Polar Bears on Ringed Seals in the Southern Beaufort Sea: Possible Significance of Changing Spring Ice Conditions - Stirling, Ian; Richardson, Evan; Thiemann, Gregory W.; Derocher, Andrew E. (ARCTIC, 2009)
In April and May 2003 through 2006, unusually rough and rafted sea ice extended for several tens of kilometres offshore in the southeastern Beaufort Sea from about Atkinson Point to the Alaska border. Hunting success of polar bears (Ursus maritimus) seeking seals was low despite extensive searching for prey. It is unknown whether seals were less abundant in comparison to other years or less accessible because they maintained breathing holes below rafted ice rather than snowdrifts, or whether some other factor was involved. However, we found 13 sites where polar bears had clawed holes through rafted ice in attempts to capture ringed seals (Phoca hispida) in 2005 through 2006 and another site during an additional research project in 2007. Ice thickness at the 12 sites that we measured averaged 41 cm. These observations, along with cannibalized and starved polar bears found on the sea ice in the same general area in the springs of 2004 through 2006, suggest that during those years, polar bears in the southern Beaufort Sea were nutritionally stressed. Searches made farther north during the same period and using the same methods produced no similar observations near Banks Island or in Amundsen Gulf. A possible underlying ecological explanation is a decadal-scale downturn in seal populations. But a more likely explanation is major changes in the sea-ice and marine environment resulting from record amounts and duration of open water in the Beaufort and Chukchi seas, possibly influenced by climate warming. Because the underlying causes of observed changes in polar bear body condition and foraging behaviour are unknown, further study is warranted. En avril et en mai des années 2003 à 2006, de la glace de mer inhabituellement raboteuse et entassée s’est étendue sur plusieurs dizaines de kilomètres au large du sud-est de la mer de Beaufort, à partir de la pointe Atkinson environ jusqu’à la frontière de l’Alaska. Les ours polaires (Ursus maritimus) avaient donc du mal à attraper des phoques malgré la chasse intense. On ne ...